2022
DOI: 10.1093/jeg/lbac025
|View full text |Cite
|
Sign up to set email alerts
|

Do preferences for urban amenities differ by skill?

Abstract: By investing in urban amenities, city-level policies often aim to attract highly skilled workers. However, studies relying on revealed preferences struggle to provide causal evidence that skilled workers value urban amenities more than less skilled workers. Therefore, we use a stated-preference experiment with hypothetical job choices between two cities that differ in wages, urban amenities and economic dynamism. We find that respondents are willing to forgo a significant fraction of their wages for better urb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…At the same time, some cities seek to depoliticise their branding strategy to avoid taking partisan stances on charged social policy debates (Belabas et al, 2020). However, some recent studies have found social diversity, openness, and tolerance are relatively less important than other amenities, including for university graduates or creative class professionals (Arntz et al, 2022; Vossen et al, 2019).…”
Section: Where Graduates Migrate and Whymentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, some cities seek to depoliticise their branding strategy to avoid taking partisan stances on charged social policy debates (Belabas et al, 2020). However, some recent studies have found social diversity, openness, and tolerance are relatively less important than other amenities, including for university graduates or creative class professionals (Arntz et al, 2022; Vossen et al, 2019).…”
Section: Where Graduates Migrate and Whymentioning
confidence: 99%
“…Revealed preference studies, usually based on official census data, estimate the relative importance of amenities based on observed demographic changes in relation to various city characteristics. Recent studies have demonstrated the potential for stated preference research to unpack migration decision-making processes and locational preferences (Buchholz, 2022), using choice experiments to overcome the endogeneity limitations of revealed preference studies (Arntz et al, 2022). For example, Koşar et al (2022) study individual preferences for several locational attributes, including income, housing characteristics, amenities, crime levels, and school quality.…”
Section: Graduate Migration Decision-makingmentioning
confidence: 99%
“…The majority of the world's population lives in urban places (Ritchie and Roser 2018;. Large cities attract people because they can offer more and better jobs, higher wages, better amenities, a variety of facilities, higher level of education and higher future prospects (Roca and Puga 2017;Jales et al 2022;Arntz et al 2023). Yet, we observe that the levels of satisfaction for urban residents are usually lower compared to residents in rural areas.…”
Section: Well-being Cities and Socio-spatial Comparisonsmentioning
confidence: 99%